2021
DOI: 10.3390/atmos12060788
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Air Pollutant Variations during COVID-19 Lockdown in a Capital City in Northwest China

Abstract: In the context of the outbreak of coronavirus disease 2019 (COVID-19), strict lockdown policies were implemented to control nonessential human activities in Xi’an, northwest China, which greatly limited the spread of the pandemic and affected air quality. Compared with pre-lockdown, the air quality index and concentrations of PM2.5, PM10, SO2, and CO during the lockdown reduced, but the reductions were not very significant. NO2 levels exhibited the largest decrease (52%) during lockdown, owing to the remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…This study and most related studies in other cities have similar findings. Same as the study by Cao, Feng and Lian et al [ 14 , 15 , 47 ], this study found an increase in O 3 values in Wuhan during the city closure and the main reason for this phenomenon may be related to the change in NOx, which is yet to be further investigated. However, this study did not take into account other factors that influence AQI, including temperature, wind, regional transport patterns and precipitation that are not identical for each year among years.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This study and most related studies in other cities have similar findings. Same as the study by Cao, Feng and Lian et al [ 14 , 15 , 47 ], this study found an increase in O 3 values in Wuhan during the city closure and the main reason for this phenomenon may be related to the change in NOx, which is yet to be further investigated. However, this study did not take into account other factors that influence AQI, including temperature, wind, regional transport patterns and precipitation that are not identical for each year among years.…”
Section: Discussionsupporting
confidence: 62%
“…However, they agreed that overall source control measures should be implemented to improve urban ambient air quality [ 17 ]. In addition, studies by Cao and Feng et al have found some negative effects of city closure, reflected in the increase in O 3 pollution [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease is pronounced in the Ruhr area and in urban areas such as Cologne, Frankfurt, Munich, and Berlin with reductions between 21% and 38%, attributable to strongly reduced road traffic and industrial production, but also to lower NO 2 levels in 2020 before the lockdown and meteorological conditions that are not further disentangled here. A detailed analysis of the lockdown effects on tropospheric NO 2 and their statistical significance considering source attributions of different sectors (Petit et al 2021;Feng et al 2021;Putaud et al 2021), adjustments to multiannual trend effects (Bekbulat et al 2020), or corrections for meteorological influences (Zhou et al 2012;Goldberg et al 2020) is out of scope of this paper. However, the presented findings are in the range of more detailed studies that consider wind corrections and adjustments to trend effects, but focus on different periods of the lockdown (e.g., Liu et al 2020;Goldberg et al 2020).…”
Section: Bluesky Flight Strategy and Scopementioning
confidence: 99%
“…Air quality is deteriorating due to anthropogenic activities (e.g. vehicle exhaust, industrial emissions, fossil fuel combustion, resident, and household smoking and heating) (Feng et al 2021 ; Ismail et al 2021 ). Exhausts from motor vehicles cause about 50% of air pollution in Iran (Ghaffarpasand et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%